Heat Treatment Technology of Porous Building Materials with Predictability of Thermophysical Properties - Baba Babanli, Mustafa; Shumska, Liubov; Leshchenko, Maryna (International Journal of Engineering and Technology, 2018)
The work is devoted to theoretical and experimental research of thermophysical features of the creation of new porous heat insulating materials, precisely: research of thermodynamic parameters of the heating processes, swelling and drying of materials; substantiation of the choice of the raw mixture method formation and determination of the optimal energy parameters of the swelling process; development of mathematical models of material heat treatment process and methods of basic technological parameters determination; development of advanced technologies for thermal protection of buildings and power equipment. Experimentally determined dependencies of technological parameters of heat treatment of the raw material mixture in the discharge, its composition, which allows obtaining material with minimal thermal conductivity. Also, the resulting dependencies ensure to find the required mode of heat treatment for the given thermophysical properties. The experimental setup has been developed, which provided to determine the basic laws of heat transfer of porous material, on the basis of which data were obtained, which allow to carry out an estimation of heat transfer and exchange characteristics of the new dispersed porous material necessary for technological calculations. A complex mathematical model of the heat energy mode of the building was created, as well as a program for solving the equations of this model, which makes it possible to determine the basic energy characteristics.Â Â